Diagnóstico inicial para la propuesta de un plan de mercadeo social para el maíz y fríjol biofortificado en instituciones y programas de seguridad alimentaria en el departamento del Cauca, Colombia - Gómez González, Luz Karime (2011)
The research project was developed in the community houses of the national Institute of Family Welfare (ICBF, its Spanish acronym) in the Department of Cauca, Colombia. The project’s principal objective was to conduct an initial diagnosis for a proposal on the social marketing of two biofortified crops—maize and common beans—in institutions and food-security programs in Cauca. The research was quantitative, qualitative, and descriptive. Data triangulation, involving different sources of information, was used to describe the market for maize and beans from different standpoints and preferences. The municipalities where the surveys were conducted were selected through variable-crossing among the 42 municipalities that form the Department of Cauca. Results yielded important data on preferences and average consumption, preferences for preparation, and the principal products used to substitute maize and beans. Moreover, the results indicated that maize and beans are significant ingredients in the Caucan diet, translating into high acceptance by consumers. Both crops are part of traditional cropping systems, thus indicating that most producers are small and medium-scale farmers. The marketing plan was designed to encompass, at first, 20% of the niches identified in one year, with a possibility of increasing over time, as both biofortified crops have the potential to replace non-biofortified maize and common beans. However, the area available in the Department of Cauca is limited, which makes reaching 100% of the market unlikely. Interinstitutional cooperation between CIAT, ICBF, and the Cauca Secretariat is key to the population adopting biofortified maize and beans. These institutions can provide monitoring, agricultural technical assistance, and effective product delivery to that part of the infant population suffering from micronutrient malnutrition.